That funny feeling [videorecording (DVD)] - Dee, Sandra; Darin, Bobby; O'Connor, Donald, 1925-2003; Thorpe, Richard, 1896-1991; Barasch, Norman; Moore, Carroll, 1913-1977 (Universal Studios Home Video, 2004)
A young and pretty maid-for-hire meets and begins dating a wealthy businessman. Embarrassed about taking him to her tiny apartment, she takes him to the home she cleans--not knowing it's really his place. He goes along with the deception until she discovers who he really is and seeks revenge.